2020
DOI: 10.1186/s13690-019-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity among school age children in Merawi town, Amhara region, Ethiopia, 2018: a community based cross-sectional study

Abstract: Background: Malnutrition with its constituents of protein energy malnutrition and micro-nutrient deficiencies continues to be a major health burden in low and middle-income countries. To end all forms of malnutrition, we need to address poverty, which is associated with the insecure supply of food and diversified nutrition. The objective of this study was to determine the level of dietary diversity and household food security among urban school-age children in Merawi town, Ethiopia. Methods: A community based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…This finding concurs with previous studies among Beninese in all age groups and settings reported to have low dietary diversity 28 39. Studies in Southwest Ethiopia3 and Amhara region, Ethiopia40 reported an inadequately diversified of 20% and 8.3%, respectively, which are lower than our study. Studies in eastern Uganda4 and South Africa,3 both reported a higher dietary diversity of 45.3% and 61%, respectively, among schoolchildren and adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding concurs with previous studies among Beninese in all age groups and settings reported to have low dietary diversity 28 39. Studies in Southwest Ethiopia3 and Amhara region, Ethiopia40 reported an inadequately diversified of 20% and 8.3%, respectively, which are lower than our study. Studies in eastern Uganda4 and South Africa,3 both reported a higher dietary diversity of 45.3% and 61%, respectively, among schoolchildren and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between household socioeconomic status and dietary diversity in this paper is in compliance with findings of previous studies 10 40. Similarly, a review concluded that the household socioeconomic status positively correlated to the dietary diversity of the schoolchildren and adolescents 4.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, Africa is the only region where the number of malnourished children continues to rise – from 50 million in 2000 to 59 million in 2018 [ 8 ]. In developing nations, undernutrition in school-age children (SAC) has been connected to poor nutritional intake, limited access to food, food insecurity in the home, hygienic habits, and family socioeconomic status [ [9] , [10] , [11] ]. Low school enrolment, high absenteeism, school dropout, poor academic performance, and poor general well-being are all frequently attributed to undernutrition at this stage [ [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%
“…The poor dietary quality is attributed to low food availability, low family income, and associated inadequate food access [ 3 , 4 , 5 , 6 , 7 ], resulting in child malnutrition. According to the cost of hunger estimates for Ethiopia, child malnutrition causes 4.4 million annual additional morbidity episodes and 28% of under-five mortality in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%